A Preliminary Study of the Temporal and Spatial Biomass Patterns of Herbaceous Vegetation Consumed by Mountain Gorillas in an Afromontane Rain Forest - Ganas, Jessica; Nkurunungi, John Bosco; Robbins, Martha M. (Biotropica, 2009)
Although many animal species consume herbaceous vegetation found in African tropical forests, little is known of the temporal and spatial availability of these plants. From September 2004 to August 2005 we conducted a study that quantified the temporal and spatial biomass availability of 20 species of herbs frequently consumed by endangered mountain gorillas at two locations (Buhoma and Ruhija) in Bwindi Impenetrable National Park, Uganda. In general, the biomass of herbs varied over the study period, but these changes were relatively small. For 12 of 18 and nine of 11 species in Buhoma and Ruhija, respectively, herb biomass differed significantly among habitat types. Of the nine species found in both locations, seven species had a higher biomass at Ruhija, one species had a higher biomass at Buhoma, and one species showed no difference. These results demonstrate that herb biomass varied little temporally but spatial differences in herb biomass were more pronounced. Future studies should investigate the variables that may influence herb phenological patterns such as rainfall, light, soil quality, previous disturbance regimes, and animal foraging and trampling damage
Keywords: Bwindi Impenetrable National Park; Gorilla beringei beringei; Habitat type; Phenology; Uganda